FORMATION AND DEVELOPMENT OF HUMAN CAPITAL THEORY (Scientific journal of the Fergana State University, 2023)
In this article, it is philosophically analyzed that the efficiency of human capital is a continuously developing force of economic and social development. The significance of the human factor as an indicator of the effectiveness of labor resources, knowledge, mental labor elements in intellectual activity, which ensures the effective and rational operation of the human factor as a factor of production, has been studied. The formation and development of human capital is based on high-quality, highly effective work and living standards.